Pengembangan Kapasitas Badan Pengawas Pemilihan Umum (Bawaslu) Provinsi Jawa Tengah Dalam Menjalankan Fungsi Pengawasan Pemilu - Ummah, Siti Muslikhatul (Universitas Negeri Semarang, 2017)
The offenses of elections law always occur at every elections in Indonesia. Central Java has the number of offenses which fluctuate and the same type of offense at every general elections. Thus, the need for capacity building Bawaslu Provinsi Jawa Tengah to exercises the supervision of elections. The research aims to describe capacity building of Bawaslu Provinsi Jawa Tengah to exercises the supervision of elections, to describe the factors that affecting capacity building of Bawaslu Provinsi Jawa Tengah to exercise the supervision of elections. The research method uses qualitative methods. The research object is Bawaslu Provinsi Jawa Tengah. The results showed that the capacity building of Bawaslu Provinsi Jawa Tengah to exercises the supervision of elections carried out through training of trainers, bimbingan teknis, rapat koordinator, recruitment and selection, and the socialization of participative supervision. The factors that affect it, among others, leadership, commitment, networks and information and communication media. The advice given is the socialization of participative supervision participatory surveillance conducted in public open spaces and improvement of regulations related by the authority of Bawaslu Provinsi Jawa Tengah to impose sanctions of the offenders election laws.